Potential of Obtaining Electrical Energy in the Tofu Waste Treatment Process Through Microbial Fuel Cell (MFC) - Syafaati, Ayu Diah; Wulan, Diana Rahayuning; Nugraha, Irwan (ALKIMIA, 2019)
Abstract - The need of energy in Indonesia was increasing and encouraging to develope some efficient renewable technology and environmental friendly researches. One of the alternative energy that can be used is Microbial Fuel Cell (MFC). Microbial Fuel Cell (MFC) works by using microorganisms to degrade organic compounds that can generate electrical energy. Several studies have been conducted on Single Chamber MFC. In this study, conducted to determine the effect of wastewater treatment through Stack Microbial Fuel Cell (MFC) on current producing. The system used carbon brush electrode, Proton Exchange Membrane (PEM) as cation exchanger, tofu liquid waste as source of substrate, and bacterial isolated tofu liquid waste as degrading organic substrate, that has known in system's ability to generate electrical energy as well as reduce COD value. Optical Density (OD) value was measured to determine the metabolic activity of bacteria, with wavelength 570 nm. The research showed that Microbial Fuel Cell (MFC) that lasted for 72 hours resulted potential of electrical current 0.96 mA at Stack MFC and Blank 0,43 mA. The acquisition of electric current Stack MFC was greater than Blank Single Chamber. In addition, it also decreased Chemical Oxygen Demand (COD) value in the range of 28-38%. Keywords - Chemical Oxygen Demand, Current, Microbial Fuel Cell , Stack MFC, Tofu liquid waste